The relational model of entrepreneurship and knowledge management toward innovation, strategy implementation and improving Islamic boarding school performance. (2nd August 2019) - Rofiaty, Rofiaty
Abstract : Purpose: The influence of entrepreneurial orientation and knowledge management on innovation, the influence of knowledge management on the implementation of strategies and the influence of entrepreneurial orientation, knowledge management, innovation, implementation of strategies to organizational performance, where the organization referred to is an Islamic boarding school. Design/methodology/approach: This research applied quantitative causal design and was an explanatory research. It was conducted at an Islamic boarding school in Malang in the period of April to December 2017. The population of this study included the managers of the pesantren, teachers and employee representatives making strategic decisions. The unit of analysis in this study consisted of Pondok Pesantren Ar Rohmah Putra, Pondok Pesantren Ar Rohmah Putri, Pondok Pesantren Al Izzah, Tazkiyah IIBS, Pondok Pesantren Darul Maghfirroh, Pondok Pesantren An Nur Putra, Pondok Pesantren An Nur Putri, PSBB MAN 3 Malang, Pondok Pesantren Ar Rifa'i Putra and Pondok Pesantren Ar Rifa'i Putri. Findings: First, entrepreneurial orientation and knowledge management have a significant and positive impact on the improvement of innovation. This means that the higher the entrepreneurial orientation and knowledge management by Islamic boarding schools, the better the innovation in business competitiveness. Second, knowledge management positively affects the strategy implementation. This means the better the knowledge management, the better the strategy implementation of within the framework of business competitiveness of Islamic boarding schools. Third, entrepreneurial orientation, knowledge management and strategy implementation have a significant effect on the improvement of performance of Islamic boarding schools. The higher the entrepreneurial orientation, knowledge management and strategy implementation, the better will be the performance of Islamic boarding schools. Originality/value: This study is one of the few studies that examine the influence of entrepreneurial orientation, knowledge management on innovation, implementation of strategies and the impact on organizational performance.